2014
DOI: 10.1080/00324728.2014.934908
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic disparities in mortality among the elderly in China

Abstract: This study examines the association of three different SES indicators (education, economic independence, and household per-capita income) with mortality, using a large, nationally representative longitudinal sample of 12,437 Chinese ages 65 and older. While the results vary by measures used, we find overall strong evidence for a negative association between SES and all-cause mortality. Exploring the association between SES and cause-specific mortality, we find that SES is more strongly related to a reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Although it is difficult to compare our results with these studies because of different study populations and how education was measured, the magnitude of education effect on mortality for older Chinese adults seems moderate. This finding is consistent with several studies in developing countries and in Asia (Liang et al, 2000;Liu et al, 1998;Luo and Xie, 2014;Zhu and Xie, 2007). In a meta-analysis of educationemortality relationship in Asia, Vathesatogkit et al (2014) found that the relationship between education and mortality varies in Asia, and it is weaker in older adults and in East Asia.…”
Section: Discussionsupporting
confidence: 91%
“…Although it is difficult to compare our results with these studies because of different study populations and how education was measured, the magnitude of education effect on mortality for older Chinese adults seems moderate. This finding is consistent with several studies in developing countries and in Asia (Liang et al, 2000;Liu et al, 1998;Luo and Xie, 2014;Zhu and Xie, 2007). In a meta-analysis of educationemortality relationship in Asia, Vathesatogkit et al (2014) found that the relationship between education and mortality varies in Asia, and it is weaker in older adults and in East Asia.…”
Section: Discussionsupporting
confidence: 91%
“…Luo and Xie [46] found that 74.5% of older adults were economically independent (i.e., their daily expenses could be paid by their retirement wage/pension or other income) in China. They also found older adults with economic independence had 26.4% lower risk of respiratory diseases mortality.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…It is likely that the educational levels of family members will have a stronger association with mortality among the elderly in China than has been observed in other countries because of the commonness of intergenerational co-residence. Several studies have examined the effect of elderly Chinese people’s own socioeconomic status on their mortality risk, 17 , 18 but the extent to which the socioeconomic status of other family members, in particular spouses and children, does or does not affect their mortality is still unclear.…”
Section: Introductionmentioning
confidence: 99%